COMPARATIVE STUDY ON EVOLUTION OF PERIODONTAL PARAMETERS IN PATIENTS WITH CHRONIC KIDNEY DISEASE BY TYPE OF NEPHROLOGIC TREATMENT - Dorina-Cerasella Şincar; Abdulla al-Shukeir; Paul Șerban Popa; Simona Bivolaru; Ovidiu Schipor; Oana Lorena Nistor; Mădălina Nicoleta Matei; Ana Maria Zaharescu (Romanian Society of Oral Rehabilitation, 2021)
Chronic renal failure is a progressive disease, characterized by the destruction of the functional units of the kidney, the nephrons. In order to prolong life, hemodialysis is the treatment chosen as an artificial means of eliminating nitrogen products and other toxic metabolic substances in the blood. This study was designed to evaluate the periodontal condition of patients with chronic renal failure treated or not by hemodialysis, considering this therapeutic method as an aggravating or contributory factor, which may lead to an increase in the pathological evolution of periodontal disease. The study was conducted in two groups: patients with chronic renal failure receiving hemodialysis - test group (D) - 26 patients with chronic renal failure receiving hemodialysis - control group (C) - 19 patients with chronic renal insufficiency not receiving hemodialysis. Of the 45 patients, 26 were treated by hemodialysis and 19 were in the control group. It can be seen that the age for both groups studied is close to 50 years. The values of the parameters studied, namely: the plaque indices, gingival index and loss of attachment, presents similar values. The greatest difference in plaque index (PI) was recorded in the hemodialysis group, 2.5 ± 0.4, compared to the control group at which the index value was 1.7 ± 0.2. The results presented showed that patients with chronic renal insufficiency receiving dialysis therapy are more susceptible to periodontal disease than those with chronic renal insufficiency but who do not receive dialysis. For this reason, especially for the first group of patients mentioned above, it is very important to maintain an optimal level of oral hygiene.